Progress achieved in EURAMET project 21GRD09 MetroPOEM: Metrology for the harmonisation of measurements of environmental pollutants in Europe - Arnold Dirk; Andreasen Rasmus; Cankur Oktay; Chambon Lucille; Christl Marcus; Corcho Alvarado José Antonio; Engin Betül Ari; Gudelis Arunas; Hain Karin; Hansen Violeta; Happel Steffen; Ioan Mihail-Razvan; et al. (EPJ Web of Conferences)
The European Green Deal’s ambition for zero pollution requires development of highly sensitive techniques to detect ultra-low amounts of pollutants and determine their isotope ratios, where mass spectrometry is a key method. The project bridges the traceability gap between activity and mass measurements – particularly estimation of mass bias – and establishes new tools for pollutant tracing. SI-traceable reference materials and measurement procedures are being developed that significantly reduce measurement uncertainty and detection limits, to enable tracking pollution sources by commonly available mass spectrometers. This project supports strategies described by the European Metrology Network on pollution monitoring and the established EMN on radiation protection. Main areas of work are: